Sprawlball : a visual tour of the new era of the NBA - Goldsberry, Kirk Patrick (Houghton Mifflin Harcourt, 2019)
"From the leading expert in the exploding field of basketball analytics, a stunning infographic decoding of the modern NBA: who shoots where, and how"--